2015
DOI: 10.5935/abc.20150092
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression, and General Psychological Distress in Patients with Coronary Slow Flow

Abstract: BackgroundThe relationship between psychiatric illness and heart disease has been frequently discussed in the literature. The aim of the present study was to investigate the relationship between anxiety, depression and overall psychological distress, and coronary slow flow (CSF).MethodsIn total, 44 patients with CSF and a control group of 50 patients with normal coronary arteries (NCA) were prospectively recruited. Clinical data, admission laboratory parameters, and echocardiographic and angiographic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
10
0
3
Order By: Relevance
“…Previous studies showed that obese and overweight people were more likely to have anxiety and depression than those with normal weight. [38] CNF patients were overweight, whereas patients with CSF were obese (as measured by BMI)[14]. In the present study, CSF severity is weakly correlated with BMI.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Previous studies showed that obese and overweight people were more likely to have anxiety and depression than those with normal weight. [38] CNF patients were overweight, whereas patients with CSF were obese (as measured by BMI)[14]. In the present study, CSF severity is weakly correlated with BMI.…”
Section: Discussionmentioning
confidence: 50%
“…[10] Moreover, some studies indicate that patients with CSF have increased psychological distress compared with patients having coronary normal flow (CNF). [14] However, to our knowledge, very few data are available on the relationship between CSF and psychological disorders; and that is the aim of this study.…”
Section: Introductionmentioning
confidence: 99%
“…4 This association makes adherence to treatment more difficult, increases hospitalizations, and elevates morbidity and mortality. 9 The coexistence between depressive and anxiety symptoms directly impacts quality of life. 10 Thus, it is essential that health professionals detect and treat such conditions early, in addition to developing new studies to define effective interventions.…”
Section: Interventionmentioning
confidence: 99%
“…Anxiety was also evaluated in a study, which identified that users with higher levels of anxiety had higher progression of cardiovascular diseases. 18 The "Verbal report of sleep alteration" was identified by the diagnosticians as a clinical indicator for the hypertensive and/or diabetic population is considered a predictor for the ND "Impaired sleep (10027226)". These findings corroborate the literature, which presents a study that, when evaluating the sleep quality of hypertensive patients, identified that hypertensive individuals have worse sleep quality, and another study that, with the objective of identifying sleep quality in diabetics, identified that sleep problems are common in this population.…”
Section: /15mentioning
confidence: 99%